Prevalence of fatigue,blood pressure, and its association to physical activity among post covid--19 university students - Chan, Yi Fei (2023)
Background and Objective: During Covid-19 pandemic, the physical activity level of an individual was drastically decreased. This situation was due to the lock down period and restrictions in place. Sports and exercise were mostly affected. Physical activity potentially could be related to a reduced level of feelings of low energy and fatigue in the general population. Regular physical activity is associated with lower blood pressure and reduced cardiovascular risk. Overall, physical activity does decrease the blood pressure. This research is aimed to investigate the prevalence of fatigue, blood pressure, and its association to physical activity among post Covid-19 university students. Methods: The sampling method used in the study was convenience sampling and the sample size was calculated to be at 367 students. Online survey form which contains two questionnaires, Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF) and International Physical Activity Questionnaire–Short Form (IPAQ-SF) was distributed to all UTAR students physically. The data collected were then analyzed using Pearson’s Chi-square test and Spearman’s correlation test in IBM SPSS software statistics version 29. Results: The total participants recruited were 206 students. The students consist of 50.5% male and 49.5% female which have mean age of 20.25±1.633. No significant association was detected between different types of fatigue and blood pressure with correlation coefficient (General=0.065, Physical=0.04, Emotional=0.064, Mental=0.026, Vigor=-0.118& Total=0.084), all p-values are >0.05. Moreover, there was also no significant association between 4 types of fatigue and level of physical activity with correlation coefficient (General=0.002, Physical=0.015, Emotional=0.056, Mental=-0.018& Total=-0.027) with all p>0.05. However, there was a significant association between vigor and level of physical activity with correlation coefficient 0.181 and p=0.009. When determining the association between blood pressure and level of physical activity, the results showed correlation coefficient 0.039, and III p>0.05.